2010
DOI: 10.1186/1471-2458-10-88
|View full text |Cite
|
Sign up to set email alerts
|

Health-related physical fitness and weight status in Hong Kong adolescents

Abstract: BackgroundThis study was designed to investigate the relation between health-related physical fitness and weight status in Hong Kong adolescents.Methods3,204 students aged 12-18 years participated in the Hong Kong Student Obesity Surveillance (HKSOS) project in 2006-2007. Anthropometric measures (height, weight) and health-related fitness (push-up, sit-up, sit-and-reach, 9-minute run) were assessed. Body mass index (BMI) was computed to classify participants into normal weight, underweight (Grade I, II/III), o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
69
5
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 43 publications
24
69
5
6
Order By: Relevance
“…Therefore, soccer clubs, which commonly develop exercise training programs, should target optimal body mass and fat. The advantage of our research was the laboratory setting where measurements took place by the same experienced staff (PhD in exercise physiology), in contrast with the field methods employed to assess physical fitness in previous research [10][11][12]26]. The disadvantage was that because of the cross-sectional design of our research, it was not possible to infer causal relationships between BMI, BF and physical fitness, and therefore, results should be regarded with caution.…”
Section: Association Of Bmi and Body Fat Percent With Physical Fitnessmentioning
confidence: 77%
See 1 more Smart Citation
“…Therefore, soccer clubs, which commonly develop exercise training programs, should target optimal body mass and fat. The advantage of our research was the laboratory setting where measurements took place by the same experienced staff (PhD in exercise physiology), in contrast with the field methods employed to assess physical fitness in previous research [10][11][12]26]. The disadvantage was that because of the cross-sectional design of our research, it was not possible to infer causal relationships between BMI, BF and physical fitness, and therefore, results should be regarded with caution.…”
Section: Association Of Bmi and Body Fat Percent With Physical Fitnessmentioning
confidence: 77%
“…The comparison between groups with different BMI has revealed that groups with lower or normal BMI perform better in physical fitness tests than do the overweight/obese or those with higher BMI [10][11][12][13][14]. However, such associations have not yet been investigated in soccer players.…”
Section: Introductionmentioning
confidence: 99%
“…Прегледом досадашњих истраживања утврђено је да постоји разлика између мушкараца и жена у погледу појединих антропометријских мера и параметара физичког фитнеса (Radu et al 2014;Parseh & Solhjoo 2015;Mak et al 2010;Czajkowska et al 2009;Andreasi et al 2010;Miyatake et al 2012;Pribis et al 2010;Arabmomeni & Alaei 2013;Koley & Kumaar 2011). Постоји разлика између испитаника мушке и женске популације у корелацијама трансверзалних антропометријских мера и флексибилности, као и обима грудног коша и снаге трбушне мускулатуре (Radu et al 2014).…”
Section: повезаност у зависности од полаunclassified
“…Статистичка анализа показује боље резултате дечака у тестовима трбушњаци и трчање 9 мин ., а слабији код теста дубоки претклон седећи. Ученици оба пола са прекомерном тежином и неухрањени, имају лошије резултате код адолесцената нормалне тежине код тестова склекови и трбушњаци (Mak et al 2010). Већина активних студенткиња (52%) у нормалном распону, а у случају ПБФ, 65% активних студенткиња је испод нормале, док је 33% у нормалним оквирима.…”
Section: повезаност у зависности од спортаunclassified
“…11 Moreover, overweight and obese adolescents exhibit poorer performance in health-related physical fitness than normalweight adolescents. 12 Although many known factors can affect bite force, as summarized above, there are also unknown biological, behavioral, and social contributing factors. 2 A study which focused on older Japanese people revealed that being overweight was significantly associated with lower bite force, 13 which indicated that bite force does not necessarily increase with body weight.…”
Section: Introductionmentioning
confidence: 99%